PENERAPAN METODE SERVQUAL DAN KANO UNTUK MENINGKATKAN KUALITAS PELAYANAN PERUMDA AIR MINUM TIRTA RAHARJA - Desma, Salsabilla Aldalia; Harahap, Anggi Syahadat; Wijayanti, Reni; Kurniawan, Iwan (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN (COMMUNITY OF RESEARCH LABORATORY), 2025)
This study examines the service quality of Perumda Air Minum Tirta Raharja using the SERVQUAL and Kano models integrated with the Customer Satisfaction Score and Adjusted Importance. The SERVQUAL analysis indicated that service performance remains below customer expectations, especially in aspects of assurance, tangibles, and responsiveness. The Kano model revealed that most attributes fall into the Must-be and One-dimensional categories, which highlights the importance of consistently fulfilling basic requirements while improving attributes that directly influence customer satisfaction. The integration with Adjusted Importance prioritized three key improvements: responsiveness and speed in handling complaints, conformity of water distribution with promised schedules, and the quality of supporting facilities. The findings emphasize that enhancing digital complaint systems, real-time distribution monitoring, and systematic infrastructure maintenance, supported by strengthened employee competence, will increase trust, satisfaction, and customer loyalty.